Investigating the influence of physical activity composition on arterial stiffness in youth. Issue 4 (3rd April 2023) - Marshall, Zoë A.; Mackintosh, Kelly A.; McNarry, Melitta A.
ABSTRACT: Physical activity is beneficial for arterial health in children but less is known about how all daily movement behaviours influence arterial stiffening. Compositional analysis can account for the co-dependent nature of these behaviours and therefore was employed to explore how the movement composition influences arterial health. Augmentation index (AIx) and pulse wave velocity were measured cross-sectionally in healthy children (n = 129; 12.4 ± 1.6 years). Time spent in sedentary, light physical activity (LPA), moderate-to-vigorous physical activity (MVPA) and asleep were derived from seven-day hip-worn accelerometry. The relative effects of individual behaviours and the overall movement composition on arterial stiffness were explored utilising compositional analysis, with predictive modelling used to predict effects of the substituting time between behaviours. Girls (n = 45, 12.1 ± 1.5yrs, 20.5 ± 3.6kg·m −2 ) had a higher AIx (+ 3.94; p  < 0.05) and accrued physical activity predominantly in LPA, whereas boys (n = 56, 12.6 ± 1.7yrs, 20.6 ± 4.0kg·m - 2) accrued physical activity predominantly in MVPA. Individual behaviours and the movement composition were not significant predictors of any measure of arterial stiffness ( P  > 0.05), and the reallocation of 20-minutes between behaviours did not elicit significant change in arterial stiffness, irrespective of sex ( P  > 0.05). The reallocation of time to MVPA from any other behaviour did not predict an improvement in arterial stiffness. This highlights the high potential dose of MVPA required to improve arterial health and the complex nature of the determinants of arterial stiffness. Highlights Movement behaviours in isolation nor combination predicted arterial stiffness in youth. The reallocation of behaviours from any other behaviour to MVPA did not affect arterial stiffness in youth. Arterial stiffness is a complex, multidimensional health parameter that does not appear to be primarily determined by physical activity levels or intensity.